The essential role of the ERK activation in large T antigen of BK polyomavirus regulated cell migration - Jiun-Wen Wang; Yi-Jung Li; Hsin-Hsu Wu; Hsiang-Hao Hsu; Ming-Yang Chang; Robert YL Wang; Ya-Chung Tian (Virus Research, 2023)
Recent studies have suggested that BK polyomavirus (BKPyV) may be associated with the development of urothelial carcinoma. In Merkel cell carcinoma, TAg and tAg are the major viral proteins of Merkel cell polyomavirus with oncogenic potential. In this study, we aimed to distinguish the role of TAg and tAg in cell migration. Our result demonstrated that ERK was phosphorylated in human renal tubular cells expressing its TAg and tAg after BKPyV infection. Treatment with the ERK inhibitor U0126 suppressed BKPyV gene expression and reduced BKPyV replication. Both TAg and tAg induced cell migration via ERK-dependent signaling. Furthermore, the expression of TAg and tAg had a significant regulatory effect on focal adhesion molecules in renal proximal tubular cells, which strongly suggests that alterations in the focal adhesion complexes are critically involved in TAg and tAg-induced cell migration. Gelatin zymography profiling revealed that TAg regulates the expression and activity of MMP-2 and MMP-9, but not tAg. Interestingly, TAg regulates the expression and activity of MMP-9 through ERK signaling, whereas MMP-2 is regulated through an ERK-independent pathway. Unbalanced ERK pathway activity is frequently observed in many cancers, while MMP proteins are usually overexpressed in aggressive tumors. These findings support the view that BKPyV is an oncogenic virus.